TETyper: a bioinformatic pipeline for classifying variation and genetic contexts of transposable elements from short-read whole-genome sequencing data. Issue 12 (22nd November 2018) - Sheppard, Anna E.; Stoesser, Nicole; German-Mesner, Ian; Vegesana, Kasi; Sarah Walker, A.; Crook, Derrick W.; Mathers, Amy J.
Abstract : Much of the worldwide dissemination of antibiotic resistance has been driven by resistance gene associations with mobile genetic elements (MGEs), such as plasmids and transposons. Although increasing, our understanding of resistance spread remains relatively limited, as methods for tracking mobile resistance genes through multiple species, strains and plasmids are lacking. We have developed a bioinformatic pipeline for tracking variation within, and mobility of, specific transposable elements (TEs), such as transposons carrying antibiotic-resistance genes. TETyper takes short-read whole-genome sequencing data as input and identifies single-nucleotide mutations and deletions within the TE of interest, to enable tracking of specific sequence variants, as well as the surrounding genetic context(s), to enable identification of transposition events. A major advantage of TETyper over previous methods is that it does not require a genome reference. To investigate global dissemination of Klebsiella pneumoniae carbapenemase (KPC) and its associated transposon Tn 4401, we applied TETyper to a collection of over 3000 publicly available Illumina datasets containing bla KPC . This revealed surprising diversity, with over 200 distinct flanking genetic contexts for Tn 4401, indicating high levels of transposition. Integration of sample metadata revealed insights into associations between geographic locations, host species, Tn 4401 sequence variants and flanking genetic contexts. To demonstrate the ability of TETyper to cope with high-copy-number TEs and to track specific short-term evolutionary changes, we also applied it to the insertion sequence IS 26 within a defined K. pneumoniae outbreak. TETyper is implemented in python and is freely available athttps://github.com/aesheppard/TETyper .